Gender and Empire The Imprisonment of Women in Eighteenth-Century Siberia. - BOURLAKOV, GWYN (Sibirica: Interdisciplinary Journal of Siberian Studies)
The article focuses on the imprisonment of elite women from the Russian metropole and women of mixed ethnic backgrounds on the Siberian frontier in the mid-eighteenth-century. Female prisoners and their monastic jailors responded to ascribed identities, positions, and circumstances dictated by imperial policies within the walls of the Dalmatov Vvedenskii Convent, which complicates our understanding of imperial interaction, gender, and empire in Siberia.